MODAL KERJA, PROFITABILITAS, DAN KINERJA PERUSAHAAN (Studi pada Perusahaan LQ-45 Tahun 2004-2013) - Utomo, Rahadian Prayogo; Ekowati, Wiwik Hidajah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The aim of this study is to gain empirical evidence on the influence of working capital towards corporate performance. Corporate performance is measured by Tobin’s q. Working capital is measured by cash conversion cycle (CCC) and net trade cycle (NTC). Profitability, represented by ROA, is used as intervening variable to connect the working capital with coporate performance. The sample of this study is non-financial corporate listed on LQ-45 in 2004 – 2013 period. The method used in data processing is Structural Equation Modeling (SEM). The results of this study are (1) working capital at low level have negative influence on corporate performance and profitability, this means that the hypothesis stating that the influence is positive rejected; (2) working capital at high level have positive influence on the performance and profitability, this means that the hypothesis stating that the influence is negative rejected; (3) the profitability have positive influence on performance, this means that the hypothesis is accepted; (4) working capital at low level have significant negative influence on the performance through an intervening variable of profitability, this means that the hypothesis stating that the influence is positive rejected; (5) working capital at high level have a not significant positive influence on performance through an intervening variable of profitability, this means that the hypothesis stating that the influence is negative rejected. Based on the results of the study, it could be stated that the higher the working capital, the lower the corporate performance trough the profitability is. The level of working capital used in Indonesia is relatively high. This can lead to reduced profitability and corporate performance. The manager should reduce the working capital to a more efficient level in order to increase the profitability and the corporate performance. Keywords: Working Capital, Cash Conversion Cycle (CCC), Net Trade Cycle (NTC), Profitability, Return on Assets (ROA), Corporate Performance, Tobin’s q, SEM